Answer:
17.5
Step-by-step explanation:
when you divide the two together you get 17.five
Answer:
6
Step-by-step explanation:
We want to expand this; (x + y)⁴
This can be written as;
(x + y)² × (x + y)²
This gives;
(x² + 2xy + y²) × (x² + 2xy + y²)
This gives;
x²(x² + 2xy + y²) + 2xy(x² + 2xy + y²) + y²(x² + 2xy + y²) = x⁴ + 2x³y + x²y² + 2x³y + 4x²y² + 2xy³ + x²y² + 2xy³ + y⁴
Simplifying gives;
x⁴ + 4x³y + 4xy³ + 6x²y² + y⁴
Thus, the coefficient of x²y² is 6
Answer:
8/25 simplified
Step-by-step explanation:
Answer:
0.24 + 0.32 =0.56
Step-by-step explanation:
Is this what you needed?
Answer:
n =7 or n = -17/3
Step-by-step explanation:
10 - |3n - 2| = -9 (subtract 10 from both sides)
- |3n - 2| = -9 - 10
- |3n - 2| = -19 (multiply both sides by -1)
|3n - 2| = 19
(3n - 2) = 19 or (3n - 2) = -19
For (3n - 2) = 19,
3n - 2 = 19
3n = 21
n =7 (answer)
For (3n - 2) = -19,
3n - 2 = -19
3n = -17
n = -17/3 (answer)